Divestiture and Its Market Reaction in a Consolidating Industry: The Global Brewing Industry. (August 2021) - Erl, Ludwig; Kiesel, Florian
Abstract: This study provides a perspective on the market performance of divestitures in the global brewing industry. In 2018, the five largest players accounted for 60% of the global beer volume. We analyze to what extent the capital market values divestitures in an industry where players usually seek efficiency gains and growth through mergers and acquisitions. Based on a sample of 61 divestiture intent announcements in the period from 1999–2018, this study shows that publicly listed brewing groups experience significant positive abnormal returns of about 1.4%. We measure the influential effect of success determinants concerning the underlying industry, the divested business, the divestiture structure, and the divestor itself. (JEL Classifications: G14, G34, L25, Q14)